Nematodes and Their Management - J. W. Noling (EDIS, 2012)
Plant parasitic nematodes are microscopic roundworms which live in the soil and attack the roots of plants. Crop production problems induced by nemotodes therefore generally occur as a result of root dysfuntion, reducing rooting volume and foraging and utilization efficiency of water and nurtients. This document is ENY625, Horticultural Sciences Department, UF/IFAS Extension. Previously published as part of the Florida Vegetable Production Handbook. This update January 2012.